Zonular defects in loxl1‐deficient zebrafish. (11th October 2021) - Zhang, Min; Sun, Shaoyang; Wang, Lei; Wang, Xu; Chen, Tianhui; Chen, Zexu; Jiang, Yongxiang
Abstract: Background: To investigate the roles of the lysyl oxidase‐like 1 ( loxl1 ) gene in zebrafish eye development and the potency of loxl1 deficiency in mimicking the ocular manifestations of exfoliation syndrome (XFS). Methods: CRISPR/Cas9 technology was used to generate a frameshift coding deletion in zebrafish loxl1 . Expression profiles and ocular manifestations of the wildtype, heterozygous mutant ( loxl1 +/− ) and homozygous mutant ( loxl1 −/− ) zebrafish were analysed in a range of developmental stages from zebrafish larvae to dissected adult zebrafish eyes. Results: The loxl1 deficiency caused zonular bundling disorders in juvenile zebrafish and accumulation of pearl‐like particles adhering to the adult zebrafish zonule. The bundles appeared to lack form and were thinner in both loxl1 +/− and loxl1 −/− zebrafish compared with the wildtype ( p < 0.01 for all Bonferroni post‐hoc analyses). The zonule of loxl1 −/− zebrafish appeared stretched, ragged and torn, with isolated fibres also detected. The particles in loxl1 −/− zebrafish were more numerous (counts: 92.33 ± 10.02/100 μm 2 vs. 58.33 ± 5.03/100 μm 2, p = 0.006), but smaller in size (diameter: 0.21 ± 0.03 μm vs. 0.43 ± 0.04 μm, p = 0.002) compared with those in loxl1 +/− . Transmission electron microscopy revealed thinning or even loss of elastic lamina in loxl1 +/− Bruch's membrane (BM) (thickness of elastic lamina: 92.94 ± 18.19 nm in the wildtype vs 35.65 ± 14.76 nm in loxl1 +/−, p = 0.003). The breakage of BM was observed in loxl1 −/− . Conclusions: The loxl1 −/− zebrafish is a promising animal model of XFS zonular pathology.